What Physical Aspects Influence Biochemical Activity in Soil in a Natural Landscape? - Sousa, Valéria Rodrigues; Zago, Leciana Menezes Souza; Ramalho, Werther Pereira; Caramori, Samantha Salomão (Fronteira: Journal of Social, Technological and Environmental Science, 2020)
The objective of this paper was to evaluate the effect of depth, seasonality and phytophysiognomies on the biochemical activity of soils in native Cerrado biome. Additionally, we listed which chemical parameters influence the activity of the microbiota and enzymatic activity in these environments. We selected eight sampling areas of Cerradão (Forest) and four areas of Cerrado (shrub land) and evaluated the chemical characteristics and biochemical activity. The depth, sampling site and seasonality directly affected soil metabolic activity. Microbial biomass carbon was influenced by interaction between soil depth and sampling site and the enzyme activity tends to be higher in the superficial layer of the soil. The analysis of redundancy showed strong influence of environmental variables (phosphorus and CTC) on the biological activity of the soil. Thus, the metabolic activity of microorganisms is highly influenced by intrinsic soil characteristics of each sampling site.